Characterization of the Rbfox3‐IRES‐iCre knock‐in mouse: Revealing gene recombination activity in neural and non‐neural peripheral tissues - Shiho Nishino; Misuzu Hashimoto; Swapna Paramanya Biswas; Natsuki Mikami; Yoshikazu Hasegawa; Hayate Suzuki; Woojin Kang; Seiya Mizuno; Kazuya Murata (FASEB BioAdvances)
Abstract In vivo cell type‐specific genetic recombination based on the Cre‐loxP system has contributed to the understanding of biological processes and diseases. Neuronal nuclei (NeuN)/RBFOX3 is a widely used mature neuron marker in developmental biology and neuroscience. Here, we generated Rbfox3‐improved Cre (iCre) knock‐in mouse model and investigated the effect of iCre knock‐in into the Rbfox3 gene and Cre recombination activity in the central nervous system (CNS) and peripheral tissues. The knock‐in of internal ribosome entry site (IRES)‐iCre cassette into the Rbfox3 3′ UTR did not affect birth rate, growth, and brain weight. In the adult brain, iCre protein expression was confirmed, whereas RBFOX3 protein expression was partially reduced in the knock‐in mice. Cre recombination analysis using R26GRR fluorescent reporter strain revealed that Rbfox3‐driven iCre‐induced gene recombination in the CNS and heart during embryonic development. In the adult brain, gene recombination was observed in neurons, however, not in other glial cells. In the peripheral tissues, iCre activity was found in the sciatic nerve and in other peripheral tissues, including the heart, bladder, and testis. We validated gene recombination rate in the germline and found that 100% recombination occurred in male germ cells and approximately 50% in female germ cells. Concludingly, Rbfox3‐iCre mice induce genetic recombination in neurons within CNS as well as in some peripheral tissues and germ cells. In addition to establishing a novel Cre mouse line, the findings of this study offer valuable insights into the development and application of mouse tools that utilize the Rbfox3 gene locus.